1982
DOI: 10.1128/aac.22.1.83
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular proteases increase tolerance of Bacillus subtilis to nafcillin

Abstract: Mutants of Bacillus subtilis capable of secreting high amounts of protease were highly tolerant to the lethal and lytic effects of nafcillin. Protease-deficient mutants were more susceptible. However, when subtilisin was added exogenously to a protease-deficient strain, the organism assumed the characteristics of nafcillin tolerance. Similarly, when phenylmethylsulfonyl fluoride, a serine protease inhibitor, was added to the tolerant strains, they became susceptible to nafcillin-induced lysis. The effects of n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

1984
1984
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 23 publications
1
8
0
Order By: Relevance
“…These data demonstrate the direct involvement of extracellular proteases in the control of cellular lysis in B. subtilis. The evidence provided here is in agreement with previous observations (Jolliffe et al 1980;Jolliffe et al 1982;Coxon et al 1991) and suggests that of the six extracellular proteases investigated, only NprE and AprE contribute significantly to the control of autolytic activity. These observations have important implications for the use of protease-deficient strains as hosts for the production of heterologous proteins; increased cellular lysis results in the liberation of intracellular proteases (and other macromolecules) which may contribute to degradation of the protein of interest.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These data demonstrate the direct involvement of extracellular proteases in the control of cellular lysis in B. subtilis. The evidence provided here is in agreement with previous observations (Jolliffe et al 1980;Jolliffe et al 1982;Coxon et al 1991) and suggests that of the six extracellular proteases investigated, only NprE and AprE contribute significantly to the control of autolytic activity. These observations have important implications for the use of protease-deficient strains as hosts for the production of heterologous proteins; increased cellular lysis results in the liberation of intracellular proteases (and other macromolecules) which may contribute to degradation of the protein of interest.…”
Section: Discussionsupporting
confidence: 92%
“…It has been proposed that extracellular proteases are involved in the control of autolysis in B. subtilis by modulating the activity of autolytic enzymes (Jolliffe et al 1980). Mutants deficient in extracellular proteases show increased rates of peptidoglycan turnover and increased susceptibility to cellular lysis due to unchecked autolytic activity (Jolliffe et al 1980;Jolliffe et al 1982;Coxon et al 1991). The absence of an energized cytoplasmic membrane can also lead to cellular autolysis (Jolliffe et al 1981).…”
Section: Introductionmentioning
confidence: 99%
“…We propose that the ponA2 and pbpX genes encode enzymes used for the formation of a peculiar type of peptidoglycan cross-link whose pathway is not well understood but may be a new drug target. Mycobacteria produce two kinds of peptide cross-links in the cell wall; one is the common DAP-Ala linkage, also called a 4-3 linkage, catalyzed by ␤-lactam-sensitive D,D-transpeptidase enzymes, and the other is an unusual DAP-DAP linkage, also called a 3-3 linkage, believed to be catalyzed by ␤-lactaminsensitive L,D-transpeptidase enzymes (25,56). The role of the 3-3 linkages is unknown, although up to 25% of the peptides are linked in this fashion in the wall of M. smegmatis (56).…”
Section: Discussionmentioning
confidence: 99%
“…One proposed mechanism was derived from the observation that rates of peptidoglycan turnover in B. subtilis are greater in extracellular-protease-deficient mutants (26). Furthermore, a secreted-protease-hyperproducing strain of B. subtilis is resistant to nafcillin (25), suggesting a protease-dependent downregulation of autolytic enzymes. In this view, ExpA might be a protease that specifically degrades an autolytic enzyme, and the loss of ExpA may result in increased autolysin activity.…”
Section: Discussionmentioning
confidence: 99%
“…The above findings show that the possibility of using B. lichenformis MML2501 in a xenobiotic environment is high owing to its tolerance to antibiotics, heavy metals and fungicides. It was reported that the B. subtilis relatively tolerant to the killing and lytic effects of a cell wall antibiotic (Jolliffe et al, 1982). Yilmaz (2003) reported that the Bacillus circulans is very much tolerant to many heavy metals and antibiotics.…”
Section: Discussionmentioning
confidence: 99%